Prohibitins: A Critical Role in Mitochondrial Functions and Implication in Diseases - Signorile, Anna (Cells, 2019)
Prohibitin 1 (PHB1) and prohibitin 2 (PHB2) are proteins that are ubiquitously expressed, and are present in the nucleus, cytosol, and mitochondria. Depending on the cellular localization, PHB1 and PHB2 have distinctive functions, but more evidence suggests a critical role within mitochondria. In fact, PHB proteins are highly expressed in cells that heavily depend on mitochondrial function. In mitochondria, these two proteins assemble at the inner membrane to form a supra-macromolecular structure, which works as a scaffold for proteins and lipids regulating mitochondrial metabolism, including bioenergetics, biogenesis, and dynamics in order to determine the cell fate, death, or life. PHB alterations have been found in aging and cancer, as well as neurodegenerative, cardiac, and kidney diseases, in which significant mitochondrial impairments have been observed. The molecular mechanisms by which prohibitins regulate mitochondrial function and their role in pathology are reviewed and discussed herein.